Science : it's changing your world. - Martin, Paul D., 1946- ([Washington, D.C.] : National Geographic Society, 1985)
Discusses scientific breakthroughs and future projections in industry, transportation, medicine, space, and other areas.
Includes index.
Bibliography: p. 103.
Keywords: Science -- Juvenile literature; Technology -- Juvenile literature; Science; Technology; Forecasting